15 sports stories! [videorecording (DVD)] (PBS Kids, 2021)
Strap on those soccer cleats, grab the bike helmets and head outside for fun and games, it's time for sports stories! In Arthur, Kate appears to be hypnotized by the soccer game on television! Then, in Daniel Tiger's Neighborhood, Dad Tiger gives Daniel his old bicycle. This DVD also features Molly and her friends from Molly of Denali raising money to attend a basketball tournament!